2023
DOI: 10.3390/plants12071521
|View full text |Cite
|
Sign up to set email alerts
|

Early Effects of Mycorrhizal Fungal Inoculum and Fertilizer on Morphological and Physiological Variables of Nursery-Grown Nothofagus alessandrii Plants

Abstract: Nothofagus alessandrii (ruil) is an endangered relict species, endemic to the Mediterranean area of Chile, and one of the most threatened trees in the country. Its natural distribution area has been greatly reduced by the effect of human activities; the remaining fragments are mostly intervened and highly deteriorated as a habitat and refuge for the associated biodiversity. In order to produce healthy and resistant nursery plants for recovery and restoration of N. alessandrii forests, this study evaluates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…The study area "14 Vueltas" is located in the commune of Curepto (−72.066104°, −35.119434°) at an approximate altitude of 196 m (above sea level) with an area of 69.95 ha, while "Agua Buena" is located in the commune of Constitución (−72.142403°, sea level) with an area of 145.69 ha. The mean annual temperature is equal to 14.2 • C, and the mean annual rainfall is 845 mm [9].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The study area "14 Vueltas" is located in the commune of Curepto (−72.066104°, −35.119434°) at an approximate altitude of 196 m (above sea level) with an area of 69.95 ha, while "Agua Buena" is located in the commune of Constitución (−72.142403°, sea level) with an area of 145.69 ha. The mean annual temperature is equal to 14.2 • C, and the mean annual rainfall is 845 mm [9].…”
Section: Study Areamentioning
confidence: 99%
“…−35.273924°) at an altitude of 333 m (above sea level) and an area of 141,33 ha; finally, "El Fin" is located in the commune of Empedrado (−72.344827°, −35.629865°) at an altitude of 341 m (above sea level) with an area of 145.69 ha. The mean annual temperature is equal to 14.2 °C, and the mean annual rainfall is 845 mm [9].…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of roots is essential for the successful establishment of seedlings during forest restoration. Mycorrhization, a technique gaining global significance in nursery seedling cultivation, has demonstrated its ability to enhance plant growth and enhance the overall plant performance when it is relocated to field settings [7]. It has also been demonstrated that inoculating seedlings or cuttings with different mycorrhizal fungi during the early stages of cultivation can affect their performance after being transplanted for reforestation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mycorrhization, a technique gaining global significance in nursery seedling cultivation, has demonstrated its ability to enhance plant growth and enhance the overall plant performance when it is relocated to field settings [7]. It has also been demonstrated that inoculating seedlings or cuttings with different mycorrhizal fungi during the early stages of cultivation can affect their performance after being transplanted for reforestation [7]. Previous studies have shown that inoculating beneficial microorganisms in the nursery can enhance seedling growth and nutrient efficiency [8][9][10].…”
Section: Introductionmentioning
confidence: 99%